Introducing Europace - R. Sutton (EP Europace, 1999)
BACKGROUND AND AIMS: Evidence supporting the use of pulsed field ablation (PFA) for ventricular arrhythmia (VA) ablation remains limited and heterogeneous, and the relationship between preclinical lesion characteristics and clinical outcomes is incompletely defined. We sought to systematically summarize preclinical lesion metrics and clinical outcomes of ventricular PFA. METHODS: We performed a systematic review and meta-analysis of preclinical and clinical studies of ventricular PFA. Preclinical studies reporting lesion depth or transmurality and clinical studies detailing procedural efficacy and safety were included. Random-effects models were used to pool lesion characteristics and clinical outcomes. RESULTS: Seventy-five studies were included (33 preclinical, 43 clinical; 355 patients). In preclinical models, mean lesion depth was 5.96mm(95%CI,5.07-6.84) in healthy endocardium and 5.19mm (95%CI,2.58-7.79) in healthy epicardium. Notably, lesion depth was quantitatively similar in models of scarred myocardium (5.96mm; 95%CI,5.39-6.53). Lesion transmurality was variable in healthy tissues (32%; 95%CI,15%-52%) but higher within scar (53%; 95%CI,36%-70%). Consistently, lesion depth was similar between PFA and RF in healthy myocardium, but greater with PFA in scarred models (within-study mean depth difference, 2.09mm; 95%CI,0.84-3.34). Greater contact force, repeated applications, and higher energy/duration settings were associated with increased lesion depth. Clinically, acute success was high for both premature ventricular complexes (PVCs,90%; 95%CI,83%-96%) and ventricular tachycardia (VT;92%; 95%CI,87%-96%) in studies with ≥3patients. Over a mean follow-up of approximately 5months, recurrence rates were 19% (95%CI,12%-28%) for PVCs and 21% (95%CI,10%-35%) for VT. The overall complication rate was 10% (95%CI,5%-17%) in studies with ≥3patients, with coronary artery spasm and conduction disturbances representing the most frequent adverse events. CONCLUSION: Ventricular PFA demonstrates high acute efficacy and encouraging mid-term outcomes, supported by preclinical evidence of favorable lesion penetration within scarred myocardium. Safety considerations-particularly coronary and conduction system effects-and the heterogeneity of preclinical evidence highlight the need for further investigation.